Adjectives in English French and Berber Kabyle: A Contrastive Study - Nacira Hocine (Revue des Sciences Humaines)
The aim of the present article is to compare and contrast the syntactic category of adjectives in three different languages: English, French and Berber Kabyle in order to delimit whether the members of the word class adjective are the same in the three languages, whether they share the same characteristics, whether they are formed through the same syntactic functions.